Perception of Lean Adoption among Emergency Department Personnel in Public Hospitals in Selangor, Malaysia - Azizul Rahman Mohamad Jamil; Mohd Rizal Abdul Manaf; Sharifa Ezat Wan Puteh; Kiran Ganesh Balakrishnan (Makara Journal of Health Research)
Background: This research aims to assess the perceptions of the staff working in emergency departments in Selangor, Malaysia, regarding the adoption of lean management and identify the factors that affect their perceptions.